(untitled) (Journal of the Sylhet Agricultural University, 2025)
The study was conducted to assess the growth and production performance of shrimp and rajpunti under mixed culture at various stocking ratios in Bagerhat district over a four-month period from March to July 2023. The experiment used randomized block design (RBD) and was designed with three treatments based on stocking ratio. Shrimp (Penaeus monodon) post larvae and fingerlings of rajpunti (Barbodes gonionotus) were stocked at a ratio of 4:3, 4:5, and 4:7/m2 in T1, T2, and T3, respectively. Shrimp and rajpunti were fed commercial diets and farm-made formulated feeds on a regular basis. Different water quality parameter was measured at ten day intervals. There were no significant differences (p > 0.05) in water quality parameters among all treatments. Higher final weight of shrimp was found in T2 (28.15 g) than T1 (27.39 g) or T3 (25.36 g). Rajpunti growth and survival rate were lower in T3, which had a high stocking ratio. T1 had higher shrimp production (674.34 kg/ha) than T2 (632.44 kg/ha) and T3 (488.24 kg/ha). Rajpunti production was substantially greater (p < 0.05) in T2 (1511.10 kg/ha) and T3 (1470.09 kg/ha) compared to T1 (923.06 kg/ha). However, the combined output and net profit of shrimp and rajpunti farming were considerably (p < 0.05) greater in T2 (2143.54 kg/ha, BDT 212309.10/ha) followed by T3 (1958.34 kg/ha, BDT 162831.50/ha) and T1 (1594.10 kg/ha, BDT 160845.90/ha). Therefore, the inclusion of rajpunti with shrimp at a stocking ratio of 4:5/m2 is recommended for dissemination among shrimp farmers in order to accelerate production while also generating a high economic benefit. J. Sylhet Agril. Univ. 12(1): 106-115, 2025